SEBARAN DAN KONDISI ANAKAN JENIS MERANTI (Shorea spp) DARI POHON INDUK DI KHDTK ULM - Dony Pratama; Gusti Syeransyah Rudy; Susilawati Susilawati (Universitas Lambung Mangkurat, 2023)
Kalimantan has tropical natural forests which are mostly dominated by the dipterocarpaceae family, which are known by the trade names: meranti (Shorea spp), bangkirai (Shorea laevis), lime (Dryobalanops aromatica), resak (Vatica wallichii), and keruing (Dipterocarpus). The Shorea clan or commonly referred to as the meranti group is one of the genera of the Dipterocarpaceae tribe that grows in the lowlands. Meranti is a commercial tree species with the main wood producer in Indonesia that has been traded since the start of natural forest exploitation in the era around 1970. Sampling of the mother tree of meranti (Shorea spp) was determined purposive sampling in the KHDTK ULM Mandiangin area with a total of 3 trees for 3 types of meranti. The observation of meranti (Shorea spp) saplings was carried out around the meranti mother tree. Data analysis was carried out to identify mother trees and natural meranti saplings by calculating tree diameter, branch-free height, total tree height, measuring canopy area, and calculating the number of meranti saplings. There are 3 types of meranti mother tree distribution in KHDTK Mandiangin (Shorea spp), namely red meranti (Shorea leprosula), white meranti (Shorea javanica), and yellow meranti (Shorea acuminatissima). Each type of meranti mother tree has various diameters, total height, branch-free height, and canopy width. The distribution of saplings from the mother meranti tree (Shorea spp) contained 3 types of meranti saplings, namely red meranti saplings with a total of 58 tillers, white meranti saplings with 167 tillers, and yellow meranti saplings with a total of 45 tillers.Kalimantan memiliki hutan alam tropis yang sebagian besar didominasi oleh famili dipterocarpaceae yang antara lain dikenal dengan nama perdagangan: meranti (Shorea spp), bangkirai (Shorea laevis), kapur (Dryobalanops aromatica), resak (Vatica wallichii) dan keruing (Dipterocarpus). Marga shorea atau yang secara umum biasa disebut dengan kelompok meranti merupakan salah satu marga dari suku dipterocarpaceae yang tumbuh di dataran rendah. Meranti merupakan jenis pohon komersil dengan penghasil kayu utama di Indonesia yang telah diperdagangkan sejak dimulainya pengusahaan hutan alam pada era sekitar tahun 1970. Pengambilan sampel pohon induk meranti (Shorea spp) ditentukan secara purposive sampling di areal KHDTK ULM Mandiangin dengan jumlah 3 pohon untuk 3 jenis meranti. Pengamatan anakan meranti (Shorea spp) dilakukan disekitar pohon induk meranti. Analisis data yang dilakukan untuk mengidentifikasi pohon induk dan anakan alam meranti dengan cara menghitung diameter pohon, tinggi bebas cabang, tinggi total pohon, pengukuran luas tajuk, dan perhitungan jumlah anakan meranti. Persebaran jenis pohon induk meranti di KHDTK Mandiangin terdapat 3 jenis meranti (Shorea spp) yaitu Meranti merah (Shorea leprosula), Meranti putih (Shorea javanica), dan Meranti Kuning (Shorea acuminatissima). Setiap jenis pohon induk meranti memiliki diameter, tinggi total, tinggi bebas cabang, dan lebar tajuk yang bervariasi. Persebaran jenis anakan dari pohon induk meranti (Shorea spp) terdapat 3 jenis anakan meranti yaitu anakan meranti merah dengan jumlah 58 anakan, anakan meranti putih dengan jumlah 167 anakan, dan anakan meranti kuning dengan jumlah 45 anakan.